Gross nitrogen transformations in tropical pasture soils as affected by Urochloa genotypes differing in biological nitrification inhibition (BNI) capacity. (December 2020) - Vázquez, Eduardo; Teutscherova, Nikola; Dannenmann, Michael; Töchterle, Paul; Butterbach-Bahl, Klaus; Pulleman, Mirjam; Arango, Jacobo
Abstract: Several tropical grasses, particularly Urochloa humidicola (Rendle) Schweick.) (Syn. Brachiaria humidicola ), have been associated with low soil nitrate content and reduced nitrogen (N) losses from pasture systems. Previous studies have detected that root exudates of certain Urochloa genotypes can inhibit ammonium oxidation in in vitro bioassay with Nitrosomonas and reduce net nitrification in soils, a phenomenon termed biological nitrification (BNI). However, net nitrification rates reflect the result of several N transformation processes that co-occur and together determine changes in NO3 − concentrations in soils. Thus, to better understand the mechanisms underlying BNI, gross rates of nitrification, ammonification and inorganic N immobilization need to be assessed. In this study we used, for the first time, stable isotopes techniques to disentangle the different gross N transformation processes that determine net nitrification rates in soil of Urochloa genotypes differing in BNI. Intact soil cores were collected from two experimental sites in Colombia under different Urochloa genotypes, classified as low-BNI and high-BNI based on net nitrification rates determined in previous studies. Soil cores were labeled with ( 15 NH4 )2 SO4 and K 15 NO3 to quantify gross N ammonification and nitrification, respectively and calculate the immobilization rates. Our results do not confirm lower gross nitrification rates under the high-BNI genotypes, despite reduced potential net nitrification rates and lower abundance of ammonia oxidising organisms, hence not supporting the widely accepted mechanism of BNI. Instead, the low potential nitrification rates could be explained by increased inorganic N immobilization under high-BNI genotypes, both in NH4 + -N and NO3 − -N form. The lack of differences might be explained by a strong N-limitation in our experiment, unlike previous BNI studies when large amounts of fertilizers were applied. Our results suggest that a combination of different mechanisms, particularly stimulation of N immobilization may be responsible for the BNI capacity observed as low NO3 − soil content and reduced N losses. Graphical abstract: Image 1 Highlights: We evaluated gross N transformations in Urochloa genotypes differing in BNI capacity. Gross nitrification was unaffected by BNI despite the contrasting net nitrification. High N immobilization could explain low NO3 − environment in high-BNI genotypes. Low N environments under high-BNI are explained by a mix of N conservative process.